Improving Operational Efficiency and Customer Service through a Web-Based Restaurant Management Information System - Friyani, Yeti (Journal of Computer Science Application and Engineering (JOSAPEN), 2026)
The restaurant industry faces increasing pressure to improve operational efficiency and deliver high quality customer service in a competitive and fast paced environment. This study aims to design and implement a web-based Restaurant Management Information System (RMIS) to address common operational challenges, including order processing delays, inventory inaccuracies, and fragmented service workflows. The system was developed using an Agile approach to ensure flexibility and alignment with user requirements. Data were collected through observation, interviews, and literature review, while system evaluation was conducted through functional testing and user feedback. The results indicate that the RMIS significantly improves order processing efficiency, enhances coordination between staff, and increases customer satisfaction through faster service and real time order tracking. These findings demonstrate that a web based RMIS is an effective solution for supporting efficient restaurant operations and improving overall service quality.